ANALISIS EFEKTIVITAS MEDIA PENYULUHAN TERHADAP PETANI PADI DI DESA TEBING TINGGI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Indra Budiman; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this research are: Identify extention media of existing and knowing the level of effectiveness extention media paddy farmer in Tebing Tinggi Village Benai District Kuantan Singingi Regency. This research used a survey method that is directly from the field , by means of face-to-face interviews. The method of respondent taking in this research is sensus. Appropriate purpose of the first research is using descriptive qualitative analysis. The purpose of the second research, the researchers wanted to see the effectiveness  extention media, can be measure by using EPIC model (Empathy, Perception, Impack and Communication) to measure the effectiveness of media extention is using by Likerts Summated Rating Scale ( LSRS ), where each choice answers were scored. Research results obtained extention media of existing in Tebing Tinggi Village. There are three types of media, extention media with a physical object, printed and “Do’a Padang” citizenry extention media. Extention media level of effectiveness by using physical objects are less effective category with an average total score of 3,57. Extention media printed form of sketches and posters are less effective hearts categories with an average total score of 2,51. “Do’a Padang” citizenry extention media  are less quite effective category with an average total score of 3,11.  Keywords: Effectiveness, EPIC Model, Extention Media